The Impact of Climate Change on the Health of Coastal Communities in Purirano Village, located in Kendari District, Konawe Regency, Southeast Sulawesi Province - Listy Handayani; Inayah Zahrah; Shinta Dwi Aryanti; Rusmawan; Wika Purnama Syair; Wa Ode Yanti; Galang; Shava Neisya Rifadha; Merlyn Vitaloka Pattinasarany (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Coastal areas are particularly vulnerable to the adverse effects of climate change, including sea level rise, coastal erosion, and increased frequency of extreme weather events. These environmental changes pose substantial risks not only to ecosystems but also to human health. In coastal communities, climate change has been associated with a heightened incidence of infectious diseases, respiratory disorders, and sanitation-related health problems. Method: This study employed an analytical observational design using a case-control approach. A total of 200 respondents were selected purposively. Data were collected using structured questionnaires that assessed the perceived health impacts of climate change, sanitation conditions, and access to health services. Descriptive and bivariate analyses were performed, with the Chi-Square test used to determine associations between climate change-related variables and public health outcomes, adopting a significance threshold of p < 0.05. Results: The findings indicate that 83.3% of respondents experiencing poor climate-related conditions reported health issues such as diarrhea, acute respiratory infections (ARI), and dengue hemorrhagic fever (DHF). Statistical analysis revealed a significant association between climate change exposure and the incidence of disease (p = 0.031). Conclusion: Climate change significantly affects the health of coastal populations in Purirano Village, contributing to the increased prevalence of diseases such as diarrhea and ARI. These health risks are exacerbated by inadequate sanitation facilities and limited access to clean water. The study confirms a statistically significant relationship between climate change and disease incidence (p < 0.05). Addressing these challenges requires integrated efforts, including community education, improvements in sanitation infrastructure, and the implementation of climate adaptation and mitigation policies involving both governmental and community stakeholders. Keywords: Climate Change, Coastal Community Health, Diarrhea, Acute Respiratory Infection, Dengue Fever, Environmental Health